A Aplicação das políticas de prevenção ao uso indevido de drogas no âmbito nacional e estadual - RIBEIRO, Victor Assunção (2022)
This research seeks to discuss the application of the policy for the prevention of misuse, attention and social reintegration of drug users and dependents at the national and state levels. To this end, we sought to provide a historical overview of the consumption of narcotics in societies; the international reaction to the fight against drugs; Brazil's dichotomous positioning in the formulation of its legislation and the impacts generated after Law 11.343/2006; prevention and assistance actions within the framework of harm reduction; the increase in therapeutic communities; the application of preventive policies in the State of Pará. Then, a research was carried out under the deductive approach in conjunction with bibliographic and documentary research. In view of this, the return of the concept of abstinence was identified as the norm of drug policy, the increase in investments by therapeutic communities, instead of investments in existing assistance policies, and the precariousness of the assistance network in Pará, either due to the lack of trained professionals. or specialized centers.